Transient respond comparison between modified droop control and virtual synchronous generator in standalone microgrid - Leng, Darith; Polmai, Sompob (My University, 2019)
The inverter-based distributed generator (DG) plays a major role to solve the worldwide energy demand increasing and the environmental concern. The DG which controls by traditionally grid-connected current control confront some problems such as lacking the grid-forming ability and inertia. Therefore, the DG could not operate in standalone, and the DG's penetration rate is limited. To address these issues, the control strategy which imitates the synchronous's generator characteristic called droop control and virtual synchronous generator (VSG) are proposed recently. Seeing the potential of both control; this paper aims to investigate the dynamic performance of modified droop control and VSG. A simulation model of parallel DGs supply to a group of the load in the form of a standalone microgrid is implemented in MATLAB/Simulink. Two case studies such as power-sharing and load transient are carried out. The results have shown that VSG provides the outperform compare to the modified droop control when a large load transition is applied.
Keywords: Distributed generator; microgrid; modified droop control; virtual synchronous generator